Effectiveness of an Information, Education, and Communication Package on Compliance to Glaucoma Medication among Caregivers of Childhood Glaucoma - Thuileiphy, T.; Mary Susaimuthu, Cecilia; Angmo, Dewang; Sihota, Ramanjit (International Journal of Nursing Research, 2023)
Aim: Patient education is important for building patients’ knowledge, practice, and self-management. The purpose of this study is to assess the effectiveness of information, education, and communication (IEC) package in educating caregivers of pediatric glaucoma. Methodology: In this prospective interventional study done at the ophthalmology department of a tertiary care hospital, a validated IEC package was administered to 60 caregivers of children attending a glaucoma clinic through interactive teaching sessions, demonstration, and return demonstration. Knowledge and practice questionnaires, observational checklist, and medication log sheets were used during the pre-test and one month after administration of IEC package (post-test). Results: The majority of the caregivers were female; the mean post-test knowledge score increased significantly, P = 0.0001. There was a significant increase in the post-test practice score, P = 0.0001. The pretest and the post-test knowledge scores had a significant association with educational status, P = 0.001, family monthly income, P = 0.001. The pre-test and the post-test practice scores had a significant association with gender, P = 0.004 and relationship to child, P = 0.003. Conclusion: This study revealed that an IEC package and short teaching session significantly increased the knowledge and practice of caregivers.